The early influence of COVID-19 pandemic-associated restrictions on pain, mood, and everyday life of patients with painful polyneuropathy. (14th November 2020) - Kersebaum, Dilara; Fabig, Sophie-Charlotte; Sendel, Manon; Sachau, Juliane; Lassen, Josephine; Rehm, Stefanie; Hüllemann, Philipp; Baron, Ralf; Gierthmühlen, Janne
Abstract : Supplemental Digital Content is Available in the Text. Validated questionnaires revealed a shift of attention from chronic pain towards the COVID-19 pandemic in patients with chronic painful polyneuropathy. Abstract: Introduction: The SARS-Cov-2 pandemic requires special attention on its psychological effects and the impact on patients with chronic pain. Objectives: This study aimed at examining the influence of the COVID-19 pandemic-associated regulations initiated by the German government on pain intensity and characteristics, emotional well-being, and everyday life of patients with painful polyneuropathy. Methods: Forty-three patients (well assessed with questionnaires before the pandemic and without change of their health status between baseline and current assessment) were investigated with validated, self-reported questionnaires and COVID-19-specific items 2 weeks after the regulations came into effect. Results: Pain intensity remained stable or even improved like the neuropathic pain symptom inventory total score (t0: 33.54 ± 20.48 vs t1: 27.38 ± 16.16, P = 0.008). Only 11.6% reported a pandemic-associated pain worsening. Rumination scores of the Pain Catastrophizing Scale were lower during t1 compared to before the pandemic regulations (t0: 7.81 ± 4.70, t1: 6.49 ± 4.39; P = 0.030). Interestingly, pain ratings for the last 7 days were higher in patients with a changed social life compared to those without (−1.63 ± 1.60 vs 0.31 ± 1.83; P = 0.01). Quality of life was decreased and helplessness increased in those with higher pain ratings. Conclusion: Results suggest a shift of attention from the chronic pain condition towards the imminent threat of a global pandemic. As the impacts of the pandemic are persistent and evolving, the development of the measured parameters in the forthcoming weeks will be of great interest.